Diet quality and snack preferences of Turkish adolescents in private and public schools - Sezer, Fatma Elif; Alpat Yavaş, İdil and Saleki, Neda and Bakırhan, Hande and Pehlivan, Merve (Frontiers in Public Health, 2024)
Socioeconomic level is one of the important factors determining diet quality. Snack preferences are affected by socioeconomic level. The objective of this research was to determine the effect of socioeconomic levels on diet quality and snack preferences among adolescents from different socioeconomic backgrounds. The study involved 118 adolescents aged between 10-18 years residing in Istanbul. A questionnaire prepared by the researchers was used to obtain information on the adolescents' dietary habits, consumption of main meals and snacks, habits, and food consumption records. The participants' food consumption was assessed using the retrospective 24-hour recall method, and diet quality was evaluated using the calculated nutrient adequacy ratio (NAR) and mean adequacy ratio (MAR). The mean age of the adolescents was 16.42±0.89 years. The number of snacks consumed in private schools was found to be higher than in public schools (p<0.05). The NAR score for vitamin C consumption was significantly higher in private schools compared to public schools (p<0.05). Although the MAR scores of adolescents in private schools were higher than those in public schools, this difference was not statistically significant. The majority of adolescents in private schools regularly consumed fresh fruit (67.2%), milk (60.3%), yogurt (60.3%), and nuts (56.9%) as snacks. In contrast, 45% of adolescents in public schools regularly consumed pastries (p<0.05). It was observed that adolescents studying in public schools had a lower tendency to prefer healthy foods for snacks compared to those in private schools. Socioeconomic level was identified as an important factor influencing eating habits during adolescence. Considering that the level of income is significantly different between the adolescents studying at private and public schools, the higher consumption of snacks by the adolescents studying at private school may be associated with higher income.